THE IMPACT OF INQUIRY-BASED LEARNING WITH COMIC MEDIA ON THE FOURTH-GRADE STUDENTS’ LEARNING INTERESTS IN ELEMENTARY SCHOOL - Sahabuddin, Erma Suryani; Irfan, Muhammad; St. Rahmadina (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
Low interest often leads students to become easily bored, making it difficult for them to understand the material being taught or studied. This study aimed to examine the impact of implementing an inquiry-based learning model, assisted by comic media, on enhancing students’ learning interests. The research employed a quasi-experimental design and was conducted at SDN 030 Tapango. The population and sample consisted of fourth-grade students (Class IVA and IVB), with 23 students in each class. Observation sheets, questionnaires, and documentation were used as research instruments. Data analysis techniques included descriptive statistics and inferential statistics, such as normality tests, homogeneity tests, and hypothesis testing. The findings revealed that the implementation of the inquiry learning model, supported by comic media, had a positive effect on increasing students’ interest in learning social and natural studies.